THE INFLUENCE OF WORK ENVIRONMENT AND WORK STRESS ON EMPLOYEE PERFORMANCE AT PT â€œSâ€ JAKARTA - Handaru, Agung Wahyu; Syafiah, Nida Hanan; Parimita, Widya (Fakultas Ekonomi, Universitas Negeri Jakarta, 2017)
The purpose of this research are: 1) To know and analyze the description for the work environment, work stress, and performance of permanent employees of PT